2021
DOI: 10.1007/s00198-021-06068-1
|View full text |Cite
|
Sign up to set email alerts
|

Fractures and fall injuries after hospitalization for seasonal influenza—a national retrospective cohort study

Abstract: In this retrospective cohort study of 6604 adults, 65 years or older, admitted with seasonal influenza at Swedish hospitals, and 330,200 age-and sex-matched controls from the general population admitted for other reasons, were included. Patients with influenza had increased risk of fall injuries and fractures compared to controls. Introduction Fractures and fall injuries often lead to disability, increased morbidity, and mortality. Older adults are at higher risk of influenza-related complications such as pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…For example, there’s an important impact on functional decline. So we know from some of our surveillance studies in Canada and elsewhere that when people are admitted to the hospital, they often don’t leave the hospital with the same degree of function that they came in with [ 7 , 8 , 10 , 11 ]. For example, up to about 20% of people can have a persistent, significant functional decline that persists even after they leave the hospital [ 12 ].…”
Section: Podcast Commentary Transcriptmentioning
confidence: 99%
“…For example, there’s an important impact on functional decline. So we know from some of our surveillance studies in Canada and elsewhere that when people are admitted to the hospital, they often don’t leave the hospital with the same degree of function that they came in with [ 7 , 8 , 10 , 11 ]. For example, up to about 20% of people can have a persistent, significant functional decline that persists even after they leave the hospital [ 12 ].…”
Section: Podcast Commentary Transcriptmentioning
confidence: 99%
“…Emerging evidence demonstrated that older adults hospitalized for influenza may have an increased risk of injury or trauma hospitalizations [ 33 ]. Therefore, the following additional negative control outcomes were included as a post‐hoc analysis: appendicitis, cataracts, eyelid disorder, hemorrhoids, herpes zoster, lipoma, and nail disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with severe chronic obstructive pulmonary disease (COPD) were at four times the risk to develop osteoporosis ( Bitar et al, 2021 ). The fracture ratio increased significantly in influenza patients after discharge ( Axelsson et al, 2022 ). Drug application in the asthma treatment process also had a potential influence on the bone mass of patients ( Chalitsios et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%